Crescimento e fenologia de espécies arbóreas com uso não madeireiro na Amazônia Central - Martins-Souza, Mikael (Instituto Nacional de Pesquisas da Amazônia - INPA, 2023)
In the Amazon rainforest, human relationships such as deforestation and fires reduce plant covering and promote climate change, CO2 emissions and biodiversity loss. These changes lead to the occurrence of extreme drought and high temperature events, it is observed that climatic seasonality has a direct influence on tree growth on tree species and also phenology. This study aimed at evaluating the growth and functional features in response to microclimatic variations in Central Amazon. The precipitation accumulated during the four years of study had a mean of 2,587.7 mm and the soil water content (SWC) with a general mean of 46.6% and with minimum and maximum values of 39.9 and 52.5% (v/v). The temperature had a mean of 25.5 °C, with minimum and maximum of (22.9 and 29.9 °C). Solar radiation (PAR) was 25,28 mol m–2 day–1, with minimum and maximum of (13.8 and 35.5 mol m–2 d–1). The mean of potential evapotranspiration was 115.8 and vapour pressure déficit (VPD) was 6.92 hPa, while the relative humidity had a mean of 79.1% and minimum and maximum of (62.79 and 91.48%). The largest trees with the highest mean monthly growth in diameter (MGD) were species L. micrantha, M. guyanensis and P. apiculatum (0.21, 0.15 and 0.15 mm month–1 ). Among the meteorological variables, rainfall and SWC positively influenced the MGD of practically all species and the VPD. The VPD was the third most influent variable in the species of this study, mainly in T. sylvestre whose values of the general mean and minimum and maximum mean were negatively affected. In relation to PAR, there was influence only on L. micrantha and M. guyanensis. Regarding the functional characteristics, the wood density did not significantly influence the species MGD. A significant relationship between of the crown radius and MGD. About phenology, no leaf change severe was observed in the canopy of the trees in the seven studied species, therefore, there was no significant effect of phenology on MGD, with the exception of P. guianensis, which was the only species to present a canopy with few leaves for a longer time and a smaller increment of the stem was found during the dry season
Keywords: Ecofisiologia de árvores; Crescimento em diâmetro do tronco